(untitled) (Fiep Bulletin - online, 2019)
Objective: The objective of this study was to evaluate the physical growth, biological maturation and motorperformance of children and adolescents in the mid-west baseball team (Atibaia, Campinas and Indaiatuba) Brazil; in the Pre-Junior category, runner-up of the Inter-selecções tournament of the year 2018. The specific objectives were: a) to compare thephysical growth with references of students of Campinas-2014 and international reference of CDC-2012; and b) to compare therelationship between motor performance and biological maturation classification. Methodology: A cross-sectional descriptivestudy was carried out. The sample consisted of twenty three (23) young male athletes between 12 and 14 years of age. Thevariables of decimal age, height, body weight, trunk-cephalic stature were evaluated. The Body Mass Index (BMI), the BodyComposition in the four components (Fat, Muscular, Bone and Residual Mass) were calculated. Biological maturation wasdetermined by the Peak Growth Rate (PVC). Motor performance was determined by abdominal muscle resistance test,horizontal jump without impulse, medical ball throw (2Kg), 30 and 50 meter run and manual pressure force. Results: It wasdetermined that (PVC) of baseball players is reached at (13.9 years) (0.4SD). In relation to the physical growth, athletes who are(-1 year of PVC) are shorter than those of the references, as regards weight and (BMI) present values slightly above the 50thpercentile. While athletes who are (in the year of PVC) have a height and weight equal to or above the 75th percentile and (BMI)below the 75th percentile.